Integrated Learning Model: A Blend of Project-Based Approach and SDLC Concepts for Software Engineering Courses, Evaluated through EUCS - Esa Fauzi; Azizah Zakiah; Yenie Syukriyah; Sy Yuliani (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
Online learning and face-to-face learning are two examples of current learning models. Online learning has the advantage of time and place flexibility as it can be conducted remotely. Meanwhile, face-to-face learning excels in the teacher-student relationship as they can meet in person. However, particularly in online learning, not all subjects can be taught optimally, such as practical courses. Blended learning is one solution for a combined learning model that can leverage both online and face-to-face learning. One of the most challenging subjects in online learning is software engineering, which requires practical exercises to write application code. There are various types of blended learning models, but we propose a blended learning model specifically based on the Software Development Lifecycle (SDLC) pattern in software engineering course materials. We do this to maximize the learning process. We also integrate blended learning with a project-based concept, as this course is well-suited for project-based learning. In evaluating this model, we analyze the satisfaction level using the end-user computing satisfaction method. The sample consists of 60 students from the Computer Science program, selected using accidental sampling. The data analysis and processing methods employed in this study include t-tests, F-tests, and multiple linear regression. The research yields a satisfaction level of 71%. The results of hypothesis testing also show that the variables Ease of Use and Timeliness have a significant positive partial impact on student satisfaction.